Implementation of sustainable business model in mini martabak business innovation - Nurhayati, Epi Liana; Agustin, Afni Alifia; Nurhayani, A'i; Oktavianti, Rika (EcoProfit: Sustainable and Environment Business, 2025)
Background: The sustainable business model of mini martabak has emerged as an innovation in the culinary industry that emphasizes sustainable principles to create unique added value and attract wider consumer interest. This study aims to discuss the application of the Sustainable Business Model to the mini martabak business, as well as its impact on local economic development and environmental preservation. Method: This study used descriptive qualitative research with a case study approach. This study focuses on an in-depth analysis of the implementation of sustainable business models applied by mini martabak business actors. Data collection techniques include in-depth interviews with business owners, direct observation of operational activities, and documentation studies on relevant business model theories. Findings: The results of this study indicate that the use of local raw materials, waste reduction, and the application of environmentally friendly practices in creating added value for consumers. In addition, strategies that prioritize awareness of sustainability have also succeeded in attracting the attention of consumers who care more about the environment. Conclusion: This research emphasizes the importance for business actors to continue to innovate and maintain product quality so that sustainable business models can succeed and grow in the long term. Novelty/Originality of this article: The study highlights the innovation of applying a sustainable business model to the mini martabak industry, emphasizing environmental awareness and local economic impact as key differentiators.